Analisis Usability Antarmuka e-learning Menggunakan Metode System Usability Scale Pada Universitas Swasta - Sri Widagdo, Adika; Pamuja, Sintia Darma (Universitas Muhammadiyah Klaten, 2025)
Online learning systems, or e-learning, have become a crucial infrastructure in higher education, enabling a better learning process. However, their success depends heavily on the usability of the interface presented to students. This study aims to evaluate the usability of the e-learning system interface at a private university to identify barriers to user interaction and provide recommendations for improvement. The evaluation was conducted using the System Usability Scale (SUS) method as a standard and reliable quantitative measurement instrument. This study involved 45 student respondents selected using purposive sampling techniques to complete the SUS questionnaire consisting of 10 statements. The results showed that the average SUS score obtained was 68.2. Based on the SUS score interpretation criteria, this value places the system in the Acceptable category based on the acceptability ranges, receiving a Grade C predicate on the grade scale, and is in the Good category based on the adjective rating. Although the system is considered suitable for use, the score position that is at the marginal threshold indicates a need for optimization in the navigation aspect and the consistency of visual elements. These findings recommend simplifying the flow of material access and improving the layout of key features to increase efficiency and user satisfaction as a reference for improvements to improve the digital learning ecosystem in the future at the university.